Analysis of Financial Reporting Practices of Pundi Amal Peduli Kasih Foundation Based on ISAK 35 - Syafitri, Nadya; Alfajri, Nopal; Uzliawati, Lia (SIMAK, 2024)
Financial reporting plays a crucial role for entities, including foundations. Foundations relying on public support require credible financial reports to maintain stakeholders' trust. This research aims to analyze the financial reporting practices of the Pundi Amal Peduli Kasih Foundation based on ISAK 35. The research method used is qualitative descriptive analysis. Data were obtained from the foundation’s financial reports covering 2020 to 2022. The findings indicate that the Pundi Amal Peduli Kasih Foundations has implemented ISAK 35 in preparing its financial statements, including the statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and notes to the financial statements.